2000
DOI: 10.1109/49.898750
|View full text |Cite
|
Sign up to set email alerts
|

Virtual time reference system: a unifying scheduling framework for scalable support of guaranteed services

Abstract: Abstract-We propose and develop a novel virtual time reference system as a unifying scheduling framework to provide scalable support for guaranteed services. This virtual time reference system is designed as a conceptual framework upon which guaranteed services can be implemented in a scalable manner using the DiffServ paradigm. The key construct in the proposed virtual time reference system is the notion of packet virtual time stamps, whose computation is core stateless, i.e., no per-flow states are required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…The virtual time reference system does not mandate any specific scheduling mechanisms to be implemented in a network domain as long as their abilities to provide delay guarantees can be characterized using the notion of error term. In fact, in [53] it is shown that almost all known scheduling algorithms can thus be characterized, be they core stateless or stateful. In addition, the virtual time reference system leads to the design of a set of new core stateless scheduling algorithms (both rate-based and delay-based).…”
Section: End-to-end Delay Bounds and Qos Abstraction Of Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The virtual time reference system does not mandate any specific scheduling mechanisms to be implemented in a network domain as long as their abilities to provide delay guarantees can be characterized using the notion of error term. In fact, in [53] it is shown that almost all known scheduling algorithms can thus be characterized, be they core stateless or stateful. In addition, the virtual time reference system leads to the design of a set of new core stateless scheduling algorithms (both rate-based and delay-based).…”
Section: End-to-end Delay Bounds and Qos Abstraction Of Datamentioning
confidence: 99%
“…In [53] it is shown that using the reference/update rule in (21) the virtual spacing and reality check properties of virtual time stamps are satisfied at every router.…”
Section: A Dynamic Packet State and Virtual Time Reference Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we have published the first papers [101,104], several new and interesting results have been reported. They include both extensions and improvements to the original CSFQ algorithm [18,25,111], and generalizations of our solution to provide guaranteed services [129,130]. In addition, DPS-like techniques have been used to develop new types of applications such as IP traceback [91].…”
Section: Contributionsmentioning
confidence: 99%